Assessment of Serum Leptin Level and Insulin Resistance in Obese Subjects - Ahsan Kazmi , Abdus Sattar,Rizwan Hashim ,Mohammad Younus (Journal of Rawalpindi Medical College, 2012)
Background: To determine the relationship between serum leptin and insulin resistance in obese Pakistani subjects. Methods: In this observational study fifty healthy obese and overweight subjects were selected by nonprobability convenience sampling. Age, sex, height, weight and body mass index (BMI) of subjects were recorded. Fasting plasma glucose, serum leptin and insulin were measured. Fifty healthy non-obese subjects served as control group. Results: Serum leptin concentration was higher in obese subjects (52.8 ± 24.6 ng/ml), with p value 0.001 than in non-obese healthy controls (6.3 ± 3.1 ng/ml). Serum leptin level was found higher in women (64.4ng/ml) than in men (40.4ng/ml) only in obese group. Insulin resistance was higher in obese subjects (11.1 ± 5.1), with p value 0.001 than control group (0.9 ± 0.4). BMI strongly correlated with leptin concentration (r = 0.59 & p = 0.001) and insulin resistance (r = 0.372 & p = 0.001) in obese group. There was highly significant correlation between serum leptin concentration and insulin resistance (r = 0.451 & p = 0.001) in this group. In the control group, there was no correlation between serum leptin concentration and insulin resistance (r = 0.166 & p = 0.249). Conclusions: Serum leptin is positively correlated with insulin resistance in obese subjects. Serum leptin level and insulin resistance are higher in obese subjects